Astma u dzieci po 5. roku życia - Majak, Paweł; Stelmach, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
High-risk birth cohorts continue to point to atopy as the main risk factor for developing asthma. However, rising trends in non-IgE-dependent asthma, such as viral-induced and exercise-induce asthma, are visible. There is a strong temporal association between viral respiratory infections and acute obstructive/asthmatic episodes. Nevertheless, the role of viral infections in the pathogenesis of asthma remains poorly characterized. The factors that could explain this association are heterogeneous and sometimes contradictory. While exercise-induced asthma seems to be less controversial, such symptoms attract attention and should also be included in the therapeutic approach. Defining the asthma phenotype seems to be the key issue in the management of this disease. Finally, in all cases we should assess the individual answer to anti-asthma treatment to confirm the asthma diagnosis.